2016
DOI: 10.1248/bpb.b15-00707
|View full text |Cite
|
Sign up to set email alerts
|

Kamikihito Ameliorates Lipopolysaccharide-Induced Sickness Behavior <i>via</i> Attenuating Neural Activation, but Not Inflammation, in the Hypothalamic Paraventricular Nucleus and Central Nucleus of the Amygdala in Mice

Abstract: Sickness behavior is a series of behavioral and psychological changes that develop in those stricken with cancers and inflammatory diseases. The etiological mechanism of sickness behavior is not known in detail, and consequently there are no established standard therapies. Kamikihito (KKT), a Kampo (traditional Japanese herbal) medicine composed of 14 herbs, has been used clinically to treat psychiatric dysfunction. Previously, we found that KKT ameliorated sickness behavior in mice inoculated with murine colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Following exposure to endotoxin (LPS), IL-6 and tumor necrosis factor α (TNFα) levels positively correlate with fMRI activation in the amygdala [Inagaki et al, 2012] and ventral striatum [Inagaki et al, 2015] in humans. In mice, it has been shown by multiple groups that LPS robustly increases pro-inflammatory cytokine production and neural activation in the hypothalamus, while decreasing dopamine [Frenois et al, 2007;Araki et al, 2016;Burfeind et al, 2016Burfeind et al, , 2018Zenz et al, 2019;Veit et al, 2021]. Additionally, administration of LPS causes upregulation of the pro-inflammatory cytokines interleukin-1β (IL-1β), TNFα, and IL-6 in the PFC [Audet et al, 2011] and causes degradation of dopamine and serotonin in the nucleus accumbens [Dölen et al, 2013;van Heesch et al, 2014;Korte-Bouws et al, 2018].…”
Section: Immune and Microbial Mediators That Exert Their Effects On S...mentioning
confidence: 99%
“…Following exposure to endotoxin (LPS), IL-6 and tumor necrosis factor α (TNFα) levels positively correlate with fMRI activation in the amygdala [Inagaki et al, 2012] and ventral striatum [Inagaki et al, 2015] in humans. In mice, it has been shown by multiple groups that LPS robustly increases pro-inflammatory cytokine production and neural activation in the hypothalamus, while decreasing dopamine [Frenois et al, 2007;Araki et al, 2016;Burfeind et al, 2016Burfeind et al, , 2018Zenz et al, 2019;Veit et al, 2021]. Additionally, administration of LPS causes upregulation of the pro-inflammatory cytokines interleukin-1β (IL-1β), TNFα, and IL-6 in the PFC [Audet et al, 2011] and causes degradation of dopamine and serotonin in the nucleus accumbens [Dölen et al, 2013;van Heesch et al, 2014;Korte-Bouws et al, 2018].…”
Section: Immune and Microbial Mediators That Exert Their Effects On S...mentioning
confidence: 99%
“…Although clinical evidence of the efficacy of KKT to treat neuroses, anxiety, or other psychogenic problems remains inadequate, recent small-scale research has revealed that it is effective for depression, anxiety, and fatigue in cancer patients (Tamada et al, 2018), and for menopausal symptoms including insomnia in patients after gynecological tumor treatment (Yoshimura et al, 2018). Similar psychotropic-like effects have been demonstrated in animal experiments; KKT suppressed depression-like behavior in lipopolysaccharidetreated mice (Araki et al, 2016), and reversed anxiety-like behaviors in mice and rats induced by an inverse agonist of GABA A receptors (Nishizawa and Yamashita, 1997). Anxiolytic effects of repeated KKT treatment were observed in non-stressed wild-type mice (Kuribara and Maruyama, 1996).…”
Section: Introductionmentioning
confidence: 74%
“…Restoration of degenerated axons and synapses may be associated with memory facilitation by this TCM 22 . Araki et al 23 . reported that Jia Wei Gui Pi Tang ameliorated sickness behaviour in mice inoculated with murine colon 26 adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 96%
“…Restoration of degenerated axons and synapses may be associated with memory facilitation by this TCM. 22 Araki et al 23 reported that Jia Wei Gui Pi Tang ameliorated sickness behaviour in mice inoculated with murine colon 26 adenocarcinoma cells. Furthermore, Adachi et al 24 reported that this TCM reduced depressivelike behaviours and hippocampus neurogenesis in chronic restraint stressed rats.…”
Section: Discussionmentioning
confidence: 99%